Longitudinal changes in antipsychotic dose in patients treated with long-acting injectable second-generation antipsychotics. (22nd January 2020) - Nakajima, Nozomi; Mizoe, Nao; Misawa, Fuminari; Yamashita, Toru; So, Ryuhei; Kitagawa, Kohei; Tanimoto, Kenichi; Kishi, Yoshiki; Fujii, Yasuo; Takeuchi, Hiroyoshi
Abstract : Only a few studies have investigated changes in the dose of long-acting injectable second-generation antipsychotics (LAI-SGAs) over the long term in the maintenance treatment of schizophrenia. In this retrospective cohort study, we examined longitudinal changes in antipsychotic dose over a 3-year period in patients with schizophrenia who had been taking LAI-SGAs for at least 1 year. We compared the total daily chlorpromazine equivalent dose of antipsychotics at 12, 24 and 36 months with the baseline dose at 3 months after initiation of LAI-SGAs. We also performed multiple regression analysis to explore factors associated with change in total daily dose 12 months after treatment initiation. A total of 154 patients fulfilled the inclusion criteria. There was no significant difference in total daily antipsychotic dose between 3 months and 12, 24 or 36 months after treatment initiation. Total daily dose was increased in 43 (27.9%), 31 (34.8%) and 22 patients (36.7%) at 12, 24 and 36 months, respectively. Age and total antipsychotic dose at 3 months were significantly negatively associated with change in total daily dose. Antipsychotic dose was basically unchanged during long-term treatment in patients treated with LAI-SGAs in the maintenance phase, although there was an increase in some patients.